The role of the psychological counselor in promoting social values among secondary school students A study on a sample of second-grade secondary students in Lattakia - بوبو منذر; حسون هنادي; الحداد نرمين (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study aimed to identify the role of the psychological counselor in promoting social values ​​among secondary education students, and to identify the differences between secondary education students about the extent to which the psychological counselor plays a role in promoting social values ​​according to the two variables of gender (male-female) and the academic branch (the literary branch - the scientific branch). The sample of the study consisted of (114) students from the second grade of secondary school in both scientific and literary branches. The most important results of the study are the sample members ’assertion that the psychological counselor plays his role in promoting the social values specified in the study tool, and among the social values mentioned by the sample members and encouraged by the psychological counselor: love, patriotism, humility, discipline, righteousness of parents, politeness, generosity, sympathy, goodness Justice, sincerity, equality, kindness. The study recommended conducting studies that include the role of the social counselor in promoting social values ​​among basic education stage pupils.